WHY ACCOUNTANT MORE ATTRACTIVE IN FINANCIAL ACCOUNTING - Natassia Irene (Perpustakaan Universitas Surabaya, 2016)
The aim of this research is to find out the reasons or factors from accountant’s perception in choosing to focus in financial accounting instead of management accounting. The method used is qualitative research, and the researcher used two samples of companies from different business entities. The researcher did interview to the accountants from two companies with some questions related with the research. The result of research shows that there are three factors why companies more focus with financial accounting. First is the size of the company and people who manage the company. Second is because financial accounting has standard, but for management accounting, companies make their own policies to arrange it. Last is because management accounting is mostly optional.